Equine Dermatophytosis: A Survey of Its Occurrence and Species Distribution among Horses in Kaduna State, Nigeria - Magdalene N. Maurice; Haruna M. Kazeem; Clara N. Kwanashie; Nanven A. Maurice; Emmanuel O. Ngbede; Helen N. Adamu; Wayuta P. Mshelia; Richard E. Edeh (Scientifica)
This study was designed to determine the occurrence and species distribution of dermatophyte from cutaneous skin lesions of horses in Kaduna State, Nigeria. A total of 102 skin scrapings were collected from 102 horses with skin lesions. Mycological studies were carried out using conventional techniques. Dermatophytes were isolated from 18 (17.6%) of the 102 samples collected. The 18 dermatophytes were distributed into 10 different species belonging to Microsporum (n=5) and Trichophyton (n=5) genera. T. verrucosum (n=4) was the most predominant species isolated followed by M. equinum (n=3), T. vanbreuseghemii (n=2), M. gypseum (n=2), and M. canis (n=2). Others include M. fulvum (n=2), T. mentagrophytes (n=1), T. equinum (n=1), T. soudanense (n=1), and M. gallinae (n=1). The present study reveals the occurrence of dermatophytes in cutaneous skin lesions of horses in Kaduna State, Nigeria. In addition for the first time in this environment the anthropophilic dermatophyte T. soudanense was isolated from horses. These findings have great economic, veterinary, and public health significance as they relate to the cost of treatment and dissemination of zoonotic dermatophytes.